Y-1=-(x-10)

Simple and best practice solution for Y-1=-(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-1=-(x-10) equation:



-1=-(Y-10)
We move all terms to the left:
-1-(-(Y-10))=0
We calculate terms in parentheses: -(-(Y-10)), so:
-(Y-10)
We get rid of parentheses
-Y+10
We add all the numbers together, and all the variables
-1Y+10
Back to the equation:
-(-1Y+10)
We get rid of parentheses
1Y-10-1=0
We add all the numbers together, and all the variables
Y-11=0
We move all terms containing Y to the left, all other terms to the right
Y=11

See similar equations:

| 4/q+7=5 | | -3x(10)=5x(-8) | | 1-3v=-29 | | 4(x+5)+3=15 | | 6x+14=6x=14 | | 9x-20=44 | | n-3/4=-4/8 | | -8x2-10x-6=-9 | | -8(u+4)=-64 | | -1=5-2w | | 6-6x=180 | | 2y+y=2 | | x5=9 | | 9^(2x-1)=27x+3 | | n2-4n+2=-2 | | y^2-6y-13=1 | | x-10=0+6x | | 8x^2+56x+12=0 | | -4x+2=2+7x | | 15.3=x-—29.23 | | 5x+3=7x+21 | | 6x2=4x+42 | | 3n-n7=25 | | -199=x-629 | | a2-3a=40 | | -7x+1=-79+3x | | 3x+1=7x-43 | | (7y+5)+(9y+3)+134=180 | | 6x-8=5x-3 | | -9-3x=4x-79 | | -4(4x+3)=4x-32 | | 5x-3x+9=36 |

Equations solver categories